(untitled) (Baghdad Science Journal, 2025)
The present study aimed to investigate the effects of alcohol and hot aqueous extracts for leaves of Adhatoda vasica on, first larval instars Musca domestica. They were exposed to the suggested concentrations of alcoholic extract which were (500, 1000, 1500, 2000) PPM while the suggested concentrations of the hot aqueous extracts (500, 1000, 1500, 2000, 2500)PPM. The alcoholic (Methanol) extract of leaves was much effective on to killing the first larval instars of the M. domestica than hot aqueous extract.